Dissecting the effects of METTL3 on alternative splicing in prostate cancer - Wang, Lin; Shi, Ling; Liang, Yonghao; Ng, Judy Kin-Wing; Yin, Chan Hoi; Wang, Lingyi; Hou, Jinpao; Wang, Yiwei; Fung, Cathy Sin-Hang; Chiu, Peter Ka-Fung; Ng, Chi-Fai; Tsui, Stephen Kwok-Wing (Frontiers in Oncology, 2023)
Although the role of METTL3 has been extensively studied in many cancers, its role in isoform switching in prostate cancer (PCa) has been poorly explored. To investigate its role, we applied standard RNA-sequencing and long-read direct RNA-sequencing from Oxford Nanopore to examine how METTL3 affects alternative splicing (AS) in two PCa cell lines. By dissecting genome-wide METTL3-regulated AS events, we noted that two PCa cell lines (representing two different PCa subtypes, androgen-sensitive or resistant) behave differently in exon skipping and intron retention events following METTL3 depletion, suggesting AS heterogeneity in PCa. Moreover, we revealed that METTL3-regulated AS is dependent on N 6 -methyladenosine (m 6 A) and distinct splicing factors. Analysis of the AS landscape also revealed cell type specific AS signatures for some genes (e.g., MKNK2) involved in key functions in PCa tumorigenesis. Finally, we also validated the clinical relevance of MKNK2 AS events in PCa patients and pointed to the possible regulatory mechanism related to m 6 A in the exon14a/b region and SRSF1. Overall, we characterize the role of METTL3 in regulating PCa-associated AS programs, expand the role of METTL3 in tumorigenesis, and suggest that MKNK2 AS events may serve as a new potential prognostic biomarker.